Picturing the Civil War: visual culture of the rank and file - Brookes, James (2020)
The American Civil War revolutionised visual culture. From 1861 to 1865, soldiers seized upon pictures as new forms of self-expression. Yet, engagement with war imagery presented both an opportunity and a dilemma. At the outset of the conflict, conventional modes of the pictorial representation of conflict were orientated towards a romantic image of war as a heroic cause. Such conventions remained powerful, but over the conflict’s course, some soldiers began to abandon these conventions, and sought new ways of representing the experience of war; others, meanwhile, continued to fortify older traditions. As soldiers faced their foes in battle, they entered a cultural contest over the war’s representation with professional picture-makers and their own comrades.